2014
DOI: 10.1007/s00224-014-9557-5
|View full text |Cite
|
Sign up to set email alerts
|

On the Parameterized Complexity of Computing Balanced Partitions in Graphs

Abstract: A balanced partition is a clustering of a graph into a given number of equal-sized parts. For instance, the Bisection problem asks to remove at most k edges in order to partition the vertices into two equal-sized parts. We prove that Bisection is FPT for the distance to constant cliquewidth if we are given the deletion set. This implies FPT algorithms for some well-studied parameters such as cluster vertex deletion number and feedback vertex set. However, we show that Bisection does not admit polynomial-size k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…This also closes the door on the complexity of these problems on trees, as the simple case when the tree is a path is in P. (B) We prove that both Tree Partitioning and Balanced Tree Partitioning are W [1]-complete. This answers an open question in [25]. We observe that, for trees, the removal of k edges results in k + 1 components.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…This also closes the door on the complexity of these problems on trees, as the simple case when the tree is a path is in P. (B) We prove that both Tree Partitioning and Balanced Tree Partitioning are W [1]-complete. This answers an open question in [25]. We observe that, for trees, the removal of k edges results in k + 1 components.…”
Section: Introductionmentioning
confidence: 72%
“…Bevern et al [25] also showed that Balanced Graph Partitioning is W [1]-hard on forests by a reduction from the Unary Bin Packing problem, which was shown to be W [1]-hard in [19]. We note that the disconnectedness of the forest is crucial to their reduction, as they represent each number x in an instance of Bin Packing as a separate path of x vertices.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…On finite connected subgraphs of the two dimensional grid without holes, the bipartitioning problem can be solved optimally in O(n 4 ) time [FW11]. Recent work by Bevern et al [vBFSS13] looks at the parameterized complexity for computing balanced partitions in graphs.…”
Section: Exact Algorithmsmentioning
confidence: 99%